Penyuluhan kepada Masyarakat tentang Pemberantasan Sarang Nyamuk (PSN) di Desa Bak Buloh, Aceh Besar. - Urip Pratama; Ambia Nurdin; Nurul Amna; Syahdi Diara; Dhiya Miranda; Rosi Amelia; Dini Akmalia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cases of Dengue Hemorrhagic Fever (DHF) in Aceh Province are currently increasing, and Aceh Besar is one of the districts that has experienced a drastic increase in the last two years. There is a need for empowerment activities to increase community knowledge so that they can carry out prevention and improve their health status independently and sustainably. The aim of this community service activity is to provide understanding to the people of Bak Buloh Village, Kuta Baro District, Aceh Besar Regency, Aceh Province, about how to effectively eradicate mosquito nests as an effort to prevent dengue fever. The methods used are lecture, discussion and question and answer methods. The results of the counseling showed that there was a significant improvement in the majority of the people of Bak Buloh Village, after being given the Mosquito Nest Eradication (PSN) counseling. It is hoped that the relevant agencies, the Kuta Baro District Health Center, the Village and Cadres, can carry out more frequent outreach regarding the Eradication of Mosquito Nests (PSN) and the impacts it causes.